Estrus Synchronization in Ugandan Cattle Herds - Mawadri, Patrick; Benda, Katali Kirungi; Mugizi, Denis; Okullo, Paul; Kanyima, Benon; Lagu, Charles; Okwee-Acai, James; Nassuna-Musoke, Maria Gorretti; Okello-Owiny, David (Journal of applied veterinary sciences, 2025)
This survey aimed to assess the breeding practices and pregnancy rates of cattle on farms that utilized artificial insemination (AI) after estrus synchronization in Uganda. Management and breeding data were collected from 297 farms using a semi-structured questionnaire and supported by breeding record reviews and AI technician interviews. Kruskal-Wallis tests were used to determine associations between breeding practices and pregnancy rates using the R software. Breed categories on the farms were exotic dairy and their crosses (64.7%), exotic beef and their crosses (15.1%), and indigenous breeds of Ankole longhorn and shorthorn Zebu (20.2%). Main breeding methods on the farms were natural mating (53.3%), AI after natural estrus (34.7%), and AI after estrus synchronization (11.9%). Estrus synchronization protocols used on the farms were Ovsynch (42.4%), 7-day Co-synch + progesterone-releasing intravaginal device (P4ID) (32.3%), Prostaglandin F2α (PG) single injection (23.4%), and 7-day Co-synch (2.4%). Mean pregnancy rates to AI after synchronization were not significantly different (P>0.05) among protocols and were 33.00%, 42.65%, 36.87%, and 41.33% for 7-day Co-synch, 7-day Co-synch+P4ID, Ovsynch, and PG single injection protocols, respectively. Mean pregnancy rates were 29.9%, 40.4%, and 42.7% for indigenous breeds, exotic beef/crosses, and exotic dairy/crosses, respectively, and significantly lower in indigenous breeds than exotic dairy/crosses (P.adj<0.001) and exotic beef breeds/crosses (P.adj=0.004). Pregnancy rates were also significantly lower on farms where the main breeding method was natural mating than AI on natural heat (P.adj=0.03) and AI after synchronization (P.adj=0.02). Ovsynch, 7-day Co-synch+P4ID, PG single injection and 7-day Co-synch were the estrus synchronization protocols used in Uganda. Estrus synchronization was more common in dairy exotic cattle than in beef exotic or indigenous cattle. Pregnancy rates with synchronized AI were lower in B. indicus than B. taurus herds.  Improvements in management and design of controlled reproductive studies are required to enhance the success of reproductive technologies in B. indicus cattle.